Pengaruh Penerapan Model Pembelajaran Jigsaw Terhadap Kemampuan Bekerjasama Peserta Didik SD Negeri 222 Manajeng Kecamatan Sibulue Kabupaten Bone - Rusyaid Rusyaid; Muh. Salim (Al-Riwayah : Jurnal Kependidikan, 2021)
The reality in the field shows that the students' ability to work together is still low and more individualistic and shows a low level of concern among them. One of the reasons is the application of learning methods by teachers which tend to be monotonous. Therefore, the purpose of this study was to obtain an overview of the application of the jigsaw learning model to students, the ability to cooperate with students, and the effect of the application of the jigsaw learning model on the ability to cooperate with students of SD Negeri 222 Manajeng, Sibulue District, Bone Regency. This research includes quantitative research by measuring the variables of the application of the jigsaw learning model and the variables of students' cooperation abilities. The instrument used in this study was a non-test instrument in the form of an observation sheet for jigsaw learning and the ability to work together given to the experimental class and the control class. The research subjects were students of class V SD Negeri 222 Manajeng, Sibulue District, Bone Regency. This research was conducted from April to May 2019. The data obtained in this study were quantitative data and were processed by descriptive analysis and inferential analysis in the form of normality test, homogeneity test, and T test. The results of this study indicate that the application of the jigsaw learning model to the participants students of SD Negeri 222 Manajeng, Sibulue District, Bone Regency, which consisted of the grouping stage, the formation of expert groups, the reciprocal teaching stage, and exhibiting works generally carried out well. The ability to cooperate with students of SD Negeri 222 Manajeng, Sibulue District, Bone Regency before the application of the jigsaw learning method was generally in the sufficient category, while after being given treatment, the application of the jigsaw learning model was in the good category. And there is an effect of the application of the jigsaw learning model on the ability to cooperate with students of SD Negeri 222 Manajeng, Sibulue District, Bone Regency